EVALUASI KINERJA PEMBANGUNAN GEDUNG VIP RSUD CIDERES KABUPATEN MAJALENGKA - Fazlur Rahman Sidiq (PROCEEDING STIMA)
The condition of project performance that is quite good is the conformity of the product to the plan that is fulfilled, the realization of costs and time is possibly lower than the plan. An approach to the ideal condition of performance evaluation is conducted as a study of the Cideres Hospital VIP building construction project with the earned value method which is one of the tools used in project management that integrates costs and time. The purpose of this study is to obtain a project performance evaluation from cost and time management with the earned value method with cost variance (CV), schedule variance (SV), SPI, CPI, EAC, and ECD indicators and find out what costs and schedules do not match from the plan also get corrective action what can be done by PT on costs and schedules that are not in accordance with the plan. The chosen research method is a quantitative approach in the form of archival analysis to the field. The Archival analysis is a quantitative study that is used to examine the application of earned values in the construction project of the Cideres Hospital VIP Building. The results of this study show ECD graphs vs. time of project completion plans and EAC vs. RAPK charts, from the analysis of accumulated time performance each month, the latest type of work is preparatory work, land, building foundation VIP building. While the type of work that has the most loss island work, the foundation of the VIP building. Then from some of the latest and disadvantaged types of work, a comparison was made between the project efforts in the field and the efforts made by experts in the field.